Access to Musculoskeletal Specialists and Resources in Free and Charitable Clinics: A Survey of Clinic Directors. Issue 6 (29th January 2013) - Khadavi, Michael J.; Matthews, Ryan L.; Gottlieb, Karen; Conway, Robert; Davis, Wade; Parker, Jerry C.
Abstract : Objective: To evaluate the capabilities and resources of free and charitable clinics in the United States to deliver musculoskeletal care to an indigent population. Design: A voluntary, anonymous, cross‐sectional survey. Setting: Electronic mailing list for the National Association of Free and Charitable Clinics in September 2011, and in person at the Annual Summit for the National Association of Free and Charitable Clinics in October 2011. At the time of survey, 427 member‐clinics were eligible for participation. Participants: One hundred forty‐five (34%) respondents were included in data analysis. Interventions: None. Main Outcome Measures: Answers to a questionnaire regarding access to musculoskeletal care. Results: The average annual clinic volume was 5690 patient visits. Low back pain was the most common orthopedic complaint. Access to musculoskeletal specialty consultants was rated as poor or worse in 83% of clinics surveyed. The majority of respondents (63%) believed that their staff was able to treat only half or fewer of the patients who presented with musculoskeletal complaints in their clinic. The resource most needed to treat these conditions was musculoskeletal physician consultants. Conclusions: Indigent populations have a strong need for musculoskeletal care, but affordable access to physiatrists and other musculoskeletal specialists is extremely limited. Personnel at surveyed clinics believed that the greatest need to improve care is better access to these specialty physicians.